Alcohol use, cigarette smoking, vaping and number of sexual partners: A cross‐sectional study of sexually active, ethnically diverse, inner city adolescents. (28th March 2021) - Bartholomew, Rosalie; Kerry‐Barnard, Sarah; Beckley‐Hoelscher, Nicholas; Phillips, Rachel; Reid, Fiona; Fleming, Charlotte; Lesniewska, Agata; Yoward, Freya; Oakeshott, Pippa
Abstract: Context: There are few UK data on the prevalence and clustering of risky behaviours in ethnically diverse adolescents. Objectives: To investigate the prevalence of reported alcohol use, smoking and vaping, and explore whether these behaviours are associated with increased numbers of sexual partners. Design: Questionnaire survey of 'Test n Treat' chlamydia screening trial participants. Setting and participants: Sexually active students attending six London technical colleges completed confidential questionnaires and provided genitourinary samples. Results: The median age of the 509 participants was 17 years (IQR: 16‐18), 47% were male, 50% were of black ethnicity, 55% reported ≥2 sexual partners in the past year (67% of males and 45% of females) and 6.2% had chlamydia infection and 0.6% gonorrhoea. Almost half (48%) reported getting drunk in the past month, 33% smoked cigarettes and 7% had ever vaped. A larger percentage of students with ≥2 sexual partners than 0‐1 partners reported getting drunk in the past month (53.7%, 144/268% versus 42.2% 94/223, adjusted prevalence ratio: 1.33, 95% confidence interval: 1.11‐1.61) and smoking cigarettes (36.6%, 100/273% versus 30.2%, 67/222, 1.34 (1.05‐1.70)). By contrast, multiple sexual partners were not associated with vaping or chlamydia infection, but numbers were small. Conclusions: We found high prevalences of risky behaviour and an association between multiple sexual partners and smoking and/or getting drunk. Findings support the introduction of compulsory sex and relationship education in UK secondary schools, including information about the adverse effects of alcohol and smoking. Public contribution: Participants helped with study design, conduct and interpretation.